Biochar as a sustainable tool for improving the health of salt-affected soils - Yanfei Yuan; Qiang Liu; Hao Zheng; Min Li; Yifan Liu; Xiao Wang; Yue Peng; Xianxiang Luo; Fengmin Li; Xiaoyun Li; Baoshan Xing (Elsevier, 2023)
Salt-affected soil has become one of the major threats to soil health. However, the evaluation of biochar amendment effects and the underlying mechanisms on the physical, chemical, and biological indicators used for assessing the health of salt-affected soils is lacking. This review summarized biochar performance and mechanisms in improving the health of salt-affected soils. Biochar addition significantly improved soil physico-chemical properties by enhancing aggregate stability (15.0-34.9%), porosity (8.9%), and water retention capacity (7.8-18.2%), increasing cation exchange capacity (21.1%), soil organic carbon (63.1%), and nutrient availability (31.3-39.9%), as well as decreasing bulk density (6.0%) and alleviating salt stress (4.1-40.0%). Following biochar incorporation, soil biological health can also be improved, particularly enhancing microbial biomass (7.1-25.8%), facilitating enzyme activity (20.2-68.9%), and ultimately increasing plant growth. To properly assess the health of salt-affected soils, it is important to select indicators related to ecological service functions including plant production, water quality, climate change, and human health. This will improve the evaluation of soil multifunctionality and enhance current soil health assessment methods. Finally, limitations and future needs of biochar research and biochar-based technologies for soil health assessment in salt-affected soils are discussed. Based on a global meta-analysis to illustrate biochar effects on salt-affected soil health indicators, this review offers valuable insights for developing sustainable biochar-based tools for remediating salt-affected soil.